2011
DOI: 10.1080/03643107.2011.614195
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Contracting and the Moderating Influence of Caseworker Role Overload on Service Provision in Child Welfare

Abstract: Although performance-based contracts have become increasingly popular in child welfare, administrators are developing these contracts with little empirically guided information about how internal work conditions may influence the services families receive. This study examines how child welfare caseworker role overload moderates associations between child welfare agencies’ use of performance-based contracting and services provided to families. Analyses using data from the National Survey of Child and Adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…A recent study using data from the National Survey of Child and Adolescent Well-Being found that in agencies with PBCs families are less likely to receive necessary social and behavioral health services when frontline workers experience role overload (Chuang, Wells, Green & Reiter, 2011). In light of findings such as these, the type of contract indicators tied to fiscal incentives/ disincentives selected, as well as the way in which an agency's other processes promote performance and outcome achievement (Garstka et al, 2012), may be of tremendous importance to frontline practice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using data from the National Survey of Child and Adolescent Well-Being found that in agencies with PBCs families are less likely to receive necessary social and behavioral health services when frontline workers experience role overload (Chuang, Wells, Green & Reiter, 2011). In light of findings such as these, the type of contract indicators tied to fiscal incentives/ disincentives selected, as well as the way in which an agency's other processes promote performance and outcome achievement (Garstka et al, 2012), may be of tremendous importance to frontline practice.…”
Section: Discussionmentioning
confidence: 99%
“…Child welfare reform in the United States in the 1990s stemmed from an increased concern over both the number of children entering and staying in foster care without movement toward a permanent family placement, and the rising cost of keeping children in state care (Chuang, Wells, Green, & Reiter, 2011). The Adoption and Safe Families Act (ASFA) of 1997 established federal standards for performance in child welfare to emphasize that the safety of children is of paramount concern.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, the need for performance-based assessments is increasing as child welfare systems search for valid and consistent metrics to examine outcomes. Most of these performance-based assessments focus on easily measured outcomes such as the placement of the child into permanent care (Chuang, Wells, Green, & Reiter, 2011;Collins-Camargo, McBeth, & Ensign, 2011). Often these assessments have been coupled with performance-based contracts that incentivize the transfer of children out of foster care and into a permanent living arrangement (Chuang, Wells, Green, & Reiter, 2011;Collins-Camargo, McBeth, & Ensign, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations